An efficient deep learning approach to classify white blood cells - Turja, Afif Ibna Kadir Khan; Habib, Ahsan; Ehsani, Kefaiat Lamia; Shabab, Zahin; Tamanna, Anika Nower (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.